2021
DOI: 10.9734/jpri/2021/v33i41a32314
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Antioxidant Activity of Salvia hispanica

Abstract: Background: There is a growing interest worldwide to identify novel functional foods able to exert important biochemical activities with low or without toxic effect. Accordingly, the use of Salvia hispanica L. (chia) a Mexican herb, has tremendously grown as an agriculture crop owing to the nutritional and medicinal values. The objective of this study was to evaluate phytochemical composition of chia seeds and prove their claim for functional properties. Materials and Methods: The determination of total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…Our findings are consistent with previous research on Salvia species in which HEE (70%) contains more total phenolics than total flavonoid content (Mocan et al 2020;Veliˇckovi´c et al 2011). Concerning the phenolic profiles of Salvia species that have been studied before (Dib et al 2021;Mocan et al 2020;Afonso et al 2019), our results agreed with the types of phenolics found but not with the amounts found.…”
Section: Resultssupporting
confidence: 93%
“…Our findings are consistent with previous research on Salvia species in which HEE (70%) contains more total phenolics than total flavonoid content (Mocan et al 2020;Veliˇckovi´c et al 2011). Concerning the phenolic profiles of Salvia species that have been studied before (Dib et al 2021;Mocan et al 2020;Afonso et al 2019), our results agreed with the types of phenolics found but not with the amounts found.…”
Section: Resultssupporting
confidence: 93%
“…Recently, much attention has been focused on the use of plant materials as natural antioxidants which can effectively replace synthetic antioxidant. It is assumed to protect humans from oxidative cell damages, resulting in the protection against several diseases (Dib et al, 2013, Rocchetti et al, 2018. The data in Table (2) show the total antioxidants activity of prickly pears cladodes extract and fruit juice.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The researchers also proved that the most abundant phenolic acid identified in seeds extract was rosmarinic acid (0.320 mg/g DW). Dib et al [ 51 ] quantified the groups of phenolic compounds in the hydromethanol extract of chia seeds. It was proved that chia seeds had a high content of total phenols (19.06 mg GAE/g DW), which were mainly represented by flavonoids (12.3 mg CE/g DW) and tannins (8.32 mg catechin equivalents (CE)/g DW).…”
Section: Discussionmentioning
confidence: 99%